Developmental regulation of Drosophila -tubulin genes. - Kalfayan, L.J.; Wensink, P.C. (Cell, 1982)
Transcripts from the four different Drosophila melanogaster alpha-tubulin genes were detected by filter hybridization experiments that used subcloned fragments from each gene as hybridization probes. These hybridization experiments demonstrated that each gene is transcribed. All of the transcripts are found on polysomes and are long enough to encode an alpha-tubulin protein. The hybridization studies were extended to examine the developmental pattern of RNA concentrations. The concentration of RNAs from the alpha 2 and alpha 4 genes vary independently and dramatically, while those from alpha 1 and alpha 3 have parallel variations. We conclude that at the RNA level of expression, two alpha-tubulin genes are regulated in parallel and two genes are not. We hypothesize that the different concentration patterns reflect different functions for the protein products of each gene.